Geochemical characteristics, hydrocarbon potential and depositional environment of the Yangye Formation source rocks in Kashi sag, southwestern Tarim Basin, NW China. (February 2020) - Wang, Jingbin; Gao, Zhiqian; Kang, Zhihong; Zhu, Dongya; Liu, Quanyou; Ding, Qian; Liu, Ziwei
Abstract: The Yangye Formation sequence is widely exposed in Kashi sag, Tarim Basin, NW China. To investigate geochemical characteristics and depositional environment of the Yangye Formation successions, 26 samples from an outcrop kzgs section in the north and 21 core samples from YD-1 well in the south were subjected to various geochemical analyses. The average TOC content is 1.87 wt % in the kzgs section and 1.36 wt % in the YD-1 well, and most samples have fairly high TOC contents (>1.0 wt %). Notably, samples in the YD-1 well are characterized by high S1, S2, HI and PG values, compared to those in the kzgs section. Based on pyrolysis data, organic matter (OM) in the kzgs section consists predominantly of type III kerogen with gas prone, whereas OM in the YD-1 well have oil/gas prone characters with dominating mixed type II/III and type III kerogen with minor type II kerogen. T max values (447–469 °C and 453–484 °C, respectively) imply that source rocks in the kzgs section are within peak to late mature stages, and samples in the YD-1 well contain late mature to post-mature OM, consistent with the results of Ro, PI, CPI, and biomarker maturity parameters. The distributions of n -alkane, isoprenoids, sterane and terpane, as well as carbon isotopes, suggest a predominance of algal, bacterial and planktonic OM, but with terrigenous higher plants influenced. However, samples in the kzgs section probably received more contributions of terrigenous and bacteria-reworked materials. Moreover, OM in the kzgs section was likely preserved in a suboxic, fresh/brackish condition, while OM from the YD-1 well was developed under a suboxic to oxygen-depleted, fresh with brackish influenced environment. There have distinct differences in organic richness, OM types and thermal maturity between the kzgs section and YD-1 well. Overall, the Yangye Formation in the whole Kashi sag still has fair to good hydrocarbon potential, and source rocks in the YD-1 well have more favorable potential to generate considerable oil and gas hydrocarbons. Highlights: The Yangye Formation source rocks both in the north and south of Kashi sag were investigated. OM types consist primarily of type II/III and III kerogen at mature to post-mature stages. OM derived from algae, bacteria and higher plants have fair to good hydrocarbon potential. Source rocks were deposited in suboxic to oxygen-depleted, fresh to brackish water conditions. There have distinct differences in geochemistry from between the north and south of Kashi sag.